1997
DOI: 10.1177/10454411970080020601
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Adhesion and Colonization

Abstract: Streptococci express arrays of adhesins on their cell surfaces that facilitate adherence to substrates present in their natural environment within the mammalian host. A consequence of such promiscuous binding ability is that streptococcal cells may adhere simultaneously to a spectrum of substrates, including salivary glycoproteins, extracellular matrix and serum components, host cells, and other microbial cells. The multiplicity of streptococcal adherence interactions accounts, at least in part, for their succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
187
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 175 publications
2
187
0
5
Order By: Relevance
“…The poorly water-soluble α--glucans are first secreted and attach to the oral surfaces. Subsequently, oral streptococci can bind to these (Jenkinson & Lamont, 1997). The glucans thus act as intramolecular bridges.…”
Section: How Do Biofilm Polysaccharides Interact ?mentioning
confidence: 99%
“…The poorly water-soluble α--glucans are first secreted and attach to the oral surfaces. Subsequently, oral streptococci can bind to these (Jenkinson & Lamont, 1997). The glucans thus act as intramolecular bridges.…”
Section: How Do Biofilm Polysaccharides Interact ?mentioning
confidence: 99%
“…Thereafter, various cell-surface antigens of mutans streptococci and their recombinant fragments or even synthetic peptides have been studied as possible candidates for dental caries vaccines [28,29]. In the recent decade, attention has become focused on three protein antigens: the surface fibrillar adhesins, the glucosyltransferases (GTF) and the glucan-binding proteins, all of which have demonstrable associations with virulence and the process of tooth surface colonization [8,12,[30][31][32]. It is demonstrated that the streptococcal surface fibrillar adhesins control attachment to tooth surfaces, the glucosyltransferases produce adhesive glucans from sucrose, and the cell-wall-associated glucan-binding proteins have the ability to bind α-1,6-glucan and may provide the receptors for glucan-mediated aggregation [33].…”
Section: Effective Targets For Anti-caries Vaccinesmentioning
confidence: 99%
“…However, the functions of saliva are not limited to the protection of the oral cavity because the mouth also serves as a reservoir and portal of entry for microorganisms that are active elsewhere in the body. These include several Streptococcus species (18), Hemophilus influenzae (19), Epstein-Barr virus, and her-pes simplex virus (20). Here, the role of saliva is not necessarily a protective one.…”
Section: Introductionmentioning
confidence: 99%